Improvement in the Surface Integrity of AISI D3 Tool Steel Using Rotary Tool Electric Discharge Machining Process. (2016) - Dwivedi, Anand Prakash; Choudhury, Sounak Kumar
Abstract: Electric Discharge Machining (EDM) is a well-established non-conventional manufacturing process which is used across the world for machining hard conducting materials having complex geometries and intricate features that cannot be machined using the conventional processes. The present research work focusses on the surface integrity improvement of the AISI D3 Tool Steel using the tool rotation during the EDM process. Surface Roughness (Ra), Micro-Cracks and Recast Layers have been examined and studied as the output parameters. The results show that the machined workpiece has a finer surface, fewer micro-cracks and thinner recast layers as compared to the stationary tool EDM process.